The Influence of the World Gold Price, the Dow Jones Islamic Market, and the Composite Stock Price Index on the Jakarta Islamic Index for the 2014 - 2018 period - Siti Chaerunisa Prastiani (EAJ (Economic and Accounting Journal), 2021)
This study aims to determine how much influence the variables of the World Gold Price and Stock Prices with proxies: Dow Jones Islamic Market (DJIM) stock prices, and the Composite Stock Price Index (IHSG), on the Jakarta Islamic Index (JII). This study uses a quantitative approach, namely data that is measured in a numerical scale, based on the 2014-2018 Time Series data relating to variables sourced from the Central Statistics Agency, the Indonesia Stock Exchange and the Directorate General of Oil and Gas. This research uses one of the SPSS Series. The variables in this study consist of World Gold Price (X1), Dow Jones Islamic Market (DJIM) (X2), Composite Stock Price Index (IHSG) (X3) against the Jakarta Islamic Index (JII) (Y). The purpose of this research is to know each variable partially or simultaneously from the variable World Gold Price, Dow Jones Islamic Market and the Jakarta Islamic Index. Research Output expected by an Accredited journal